The Spirit of Mattola Palallo in Educating Children of Farmers’ Family in Bulutellue Village Sinjai Regency - Abdul Rahman; Najamuddin Najamuddin; Nurlela Nurlela (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research was conducted to reveal the efforts of parents in Bulutellue Village, especially from the farming community in nurturing their children based on the spirit of mattola palallo. The spirit of mattola palallo is related to the expectations of parents for their children to be able to achieve a standard of living that exceeds the lives of their parents both in terms of education and economic welfare. The researcher used a qualitative method where data were collected through observation and interviews. The results showed that the efforts of parents in nurturing their children with the spirit mattola palallo approach were taken by introducing the main values of Bugis culture, namely lempu (honest), adele (fair), macca (scholar), and sitinaja (proper). The spirit of mattola palallo is also instilled in children based on the conditions of the times that demand collaboration in solving problems while achieving a prosperous life.